1980
DOI: 10.1901/jaba.1980.13-119
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mentally Retarded Adults to Time‐manage in a Vocational Setting

Abstract: Three retarded adults who had minimal ability to tell time were trained to "time-manage." Each was given a card with clock face representations on which the hands of the clock were drawn, representing each trainee's assigned lunch and break times. Instruction was given before work to perform each of the required behaviors when the "real" clock matched the clock faces. Praise was given following correct responses, and reprimands, instruction, and, in some instances, delay or omission of the scheduled activity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 13 publications
1
33
0
Order By: Relevance
“…The relevance of these results is clear in view of the fact that printed notes and watches may be the simplest and most normal means whereby a work place can provide instructions and time cues (cf. Martin et al, 1987;Sowers, Rusch, Connis, & Cummings, 1980). For nonreading subjects, printed notes provide messages that need to be translated.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of these results is clear in view of the fact that printed notes and watches may be the simplest and most normal means whereby a work place can provide instructions and time cues (cf. Martin et al, 1987;Sowers, Rusch, Connis, & Cummings, 1980). For nonreading subjects, printed notes provide messages that need to be translated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many types of sheltered work activities and home living skills require that a series of behaviors be performed in a repetitious but evenly-paced manner. Sometimes it is observed that an individual's performance deteriorates after acquisi tion has occurred (Liberty, Haring, & Martin, 1981;Sowers, Rusch, Connis, & Cummings, 1980). In these situations, teacher-paced instruction may be an effec tive procedure to use in reestablishing appropriate pat terns of performance.…”
Section: Discussionmentioning
confidence: 99%
“…In a minority of the studies, although the authors noted positive results, these interpretations were not supported by a PND that was correlated with a high degree of effectiveness. A lack of correspondence between PND and author interpretation of the data was found in four studies (Banda and Kubina 2006;Palmen et al 2012;Flannery and Horner 1994;Sowers et al 1980). For example, Banda and Kubina (2006) cited positive results in decreasing noncompliance to transition with one student with ASD.…”
Section: Comments On Overall Effectivenessmentioning
confidence: 99%
“…Four studies were identified that implemented consequencebased strategies to teach transition skills (Carden-Smith and Fowler 1984;Connell et al 1993a, b;Sowers et al 1980). For example, Carden-Smith and Fowler (1984) examined the effects of a token economy on the transition behavior of six children with language and developmental delays in a classroom setting.…”
Section: Consequence-based Strategies For Teaching Transition-relatedmentioning
confidence: 99%